Error Control in Distributed Node Self-Localization. (24th March 2008) - Liu Liu, Juan Juan; Zhang Zhang, Ying Ying
Abstract : Location information of nodes in an ad hoc sensor network is essential to many tasks such as routing, cooperative sensing, and service delivery. Distributed node self-localization is lightweight and requires little communication overhead, but often suffers from the adverse effects of error propagation. Unlike other localization papers which focus on designing elaborate localization algorithms, this paper takes a different perspective, focusing on the error propagation problem, addressing questions such as where localization error comes from and how it propagates from node to node. To prevent error from propagating and accumulating, we develop an error-control mechanism based on characterization of node uncertainties and discrimination between neighboring nodes. The error-control mechanism uses only local knowledge and is fully decentralized. Simulation results have shown that the active selection strategy significantly mitigates the effect of error propagation for both range and directional sensors. It greatly improves localization accuracy and robustness.